Convergence of the 2-Point block backward differentiation formulas. - Ibrahim, Zarina Bibi; Suleiman , Mohamed; Othman, Khairil Iskandar; Mohd Nasir, Nor Ain Azeany (Hikari Ltd, 2011)
In this paper, the 2-point Block Backward Differentiation Formulas (BBDF) methods proposed by Zarina et al. [8] for the numerical solution of initial value problems in Ordinary Differential Equations (ODEs) are reviewed. The zero stability and consistency which are necessary conditions for convergence of the BBDF methods are studied. The order of the method is also determined.